Velimir Chlebnikov in Italy, before Ripellino - Luca Cortesi (Studi Slavistici)
The purpose of this contribution is to present and discuss two Italian translations of two different prose works by Velimir Chlebnikov, published in 1934 and 1943 respectively, in a period prior to Ripellino’s translation, which is generally considered the starting point of the diffusion of Chlebnikov’s output in Italy. The brief analysis of these two translated texts aims to contribute to the reconstruction of the history of the reception of Chlebnikov’s works in Italy.